Effect of Microwave Power and Extraction Time on Crude Palm Oil Quality Using Microwave-Assisted Extraction Process - Norashikin Ahmad Zamanhuri; Norazah Abd Rahman; Noor Fitrah Abu Bakar (International Journal of Renewable Energy Development, 2021)
The aim of this study is to evaluate microwave-assisted extraction at several microwave power and extraction time in extracting oil palm products, such as crude palm oil (CPO) and palm fatty acid (PFA) composition. The exposure time was shortened and overheating was avoided when sterilized mesocarp exposed to microwave prior to Soxhlet extraction in order to obtain good quality oil. The effects of CPO extraction and PFA composition on the distillate produced were investigated. Gas chromatography coupled with mass spectrometry (GC-MS) was used for the determination and quantification of PFA composition in the distilled products. Scanning electron microscopy (SEM) reveals that the microwave-assisted extraction technique had efficiently assisted in the release of oil by breaking down the mesocarp cell structure. To fill the research gap of microwave-assisted sterilization in the previous research, microwave-assisted extraction was introduced, in which two processes (i.e., extraction and drying) were conducted in one equipment. Oil yield and color, free fatty acids (FFA), Deterioration of Bleachability Index (DOBI), and carotene contents of the CPO were quantified. At 100 W, the extraction of CPO demonstrated 64% yield produced, with chemical properties of 0.301% FFA, 3.53 DOBI and 1132 ppm carotene with final temperature of 76.2°C during microwave-assisted extraction. The optimum condition for extracting PFA distillate was 300 W for 30 min of exposure time. Additionally, distillate obtained at the optimum condition using microwave-assisted extraction consisted of high palmitic acid (C16:0), caramel-like aroma, and possessed a sweet fragrance.